Determination and utilization of wind energy potential for Turkey - Ilkilic, Cumali; Turkbay, Ismail (Pergamon-Elsevier Science Ltd, 2010)
In this study, potential and development of wind energy systems in Turkey were studied. The potential and current usage was reviewed. The objective of the study is to investigate the wind energy plants and projects in Turkey. The wind energy potential of various regions and the exploitation of the wind energy were investigated by analyzing wind data measured as hourly time series in the windy locations. The wind data used in this study were taken from Electrical Power Resources Survey and Development Administration (EIEI) for the year 2004. Nurdagi, Karabiga, Datca, Bandirma, Antakya, Mardin, and Kumkoy areas were found to be the most suitable areas for wind energy systems by their wind densities; Sinop, Gokceada, and Siverek are following these areas. The results indicate that the investigated sites have fairly satisfactory wind energy potential for the utilization. (c) 2010 Elsevier Ltd. All rights reserved.
Keywords: Wind; Wind energy; Renewable energy; Wind plants